2023
DOI: 10.1021/jacs.3c03611
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to 2,2-Disubstituted Indolines via Dearomative Indolic-Claisen Rearrangement: Concise, Enantioselective Total Synthesis of (+)-Hinckdentine A

Abstract: The construction of 2,2-disubstituted indolines has long presented a synthetic challenge without any general solutions. Herein, we report a robust protocol for the dearomative Meerwein− Eschenmoser−Claisen rearrangement of 3-indolyl alcohols that provides efficient access to 2-substituted and 2,2-disubstituted indolines. These versatile subunits are useful for natural product synthesis and medicinal chemistry. The title [3,3] sigmatropic rearrangement proceeds in generally excellent yield and transfers the C3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 87 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…and heating to between 60 ˚C and 100 ˚C. Following this procedure, in the C(3')-F series, inclusion of Ph, 4-MeC6H4-, 4-MeOC6H4 and 4-F3CC6H4substituted allylic ethers, as well as 4-Cl, 5-F, 5-NO2, 5-MeO and 6-Cl substituents within the oxindole were tolerated, giving the corresponding [1,2]-Wittig products (46)(47)(48)(49)(50)(51)(52)(53)(54) with good to excellent enantioselectivity (91:9 to 97:3 er). In the C(3')-H series, variation of the aryl substituent within the allylic ether showed that Ph, 4-MeOC6H4, 4-F3CC6H4, 4-FC6H4, 2-MeOC6H4, 1-naphthyl and 2-naphthyl-substitution, heteroaromatic 3thienyl and C(2')-methyl substitution, alongside 4-Cl, 5-OMe and 6-Br substituents within the oxindole were tolerated, allowing the formation of enantioenriched [1,2]-Wittig rearrangement products 45, 55-65 (87:13 to 95:5 er).…”
Section: Phmentioning
confidence: 99%
See 1 more Smart Citation
“…and heating to between 60 ˚C and 100 ˚C. Following this procedure, in the C(3')-F series, inclusion of Ph, 4-MeC6H4-, 4-MeOC6H4 and 4-F3CC6H4substituted allylic ethers, as well as 4-Cl, 5-F, 5-NO2, 5-MeO and 6-Cl substituents within the oxindole were tolerated, giving the corresponding [1,2]-Wittig products (46)(47)(48)(49)(50)(51)(52)(53)(54) with good to excellent enantioselectivity (91:9 to 97:3 er). In the C(3')-H series, variation of the aryl substituent within the allylic ether showed that Ph, 4-MeOC6H4, 4-F3CC6H4, 4-FC6H4, 2-MeOC6H4, 1-naphthyl and 2-naphthyl-substitution, heteroaromatic 3thienyl and C(2')-methyl substitution, alongside 4-Cl, 5-OMe and 6-Br substituents within the oxindole were tolerated, allowing the formation of enantioenriched [1,2]-Wittig rearrangement products 45, 55-65 (87:13 to 95:5 er).…”
Section: Phmentioning
confidence: 99%
“…Overall, both the constrained cyclic transition state (ΔG ‡ = 56.9 kcal•mol −1 ) and the homolytic diradical fragmentation/recombination pathway (ΔG ‡ = 63.2 kcal•mol −1 ) were significantly disfavoured compared to an ionic fragmentation/recombination pathway (ΔG ‡ = 2.0 kcal•mol −1 ). Fig 5B shows a free energy surface for the ionic fragmentation/recombination pathway from deprotonated intermediate 66 to product 67 46,47 . This stepwise dissociative process proceeds through bond cleavage via TS A that generates a delocalised allylic anion and isatin, that recombines in an effectively barrierless process to generate 67.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…16 Synthesis of this valuable heterocycle attracts long-term interest, since the concise formation of the quaternary carbon center is challenging and no general solutions have been recorded. 17 Two pivotal strategies for synthesizing this skeleton are (A) oxidative dearomatization of pre-existing 2-substituted indole 18 and (B) annulation of pre-prepared o -nitroalkyne. 19 In addition, a step-wise Dieckmann condensation of Ugi adducts and [3,3] sigmatropic rearrangements have recently emerged as representative alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, a step-wise Dieckmann condensation of Ugi adducts and [3,3] sigmatropic rearrangements have recently emerged as representative alternatives. 17,20 Despite these significant contributions, a straightforward modular synthesis of 2,2-disubstituted indolin-3-ones from readily available starting materials is conceptually new yet still unexploited. Herein, we report our endeavor aiming to address these synthetic challenges by diverting the Mannich reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…We commenced with investigating the MECR reaction conditions (Scheme ). Based on the literature and our previous work, we chose commercially available phthaloyl tryptamine 10 as starting point. It was first activated by N -chlorosuccinimide (NCS) under basic conditions (DABCO), giving rise to intermediate I , which upon protonation with methanesulfonic acid (MsOH) became more electrophilic.…”
mentioning
confidence: 99%